Tabarruj in the Qur'an (Analytical Study of Surah Al-Ahzab Verse 33 According to Tafsir Al-Munir) - Mohammad, Shafwatun Nada; Rhain, Muhammad Ainur (Universitas Muhammadiyah Surakarta, 2023)
The problem with Tabarruj is that there are many women among us nowadays who dress up too much, which can cause crime. Many women today follow fashion, and it can endanger them. There are many phenomena of women not wearing the hijab, being open, and exposing their private parts to men who are dressed up excessively and can cause crimes. Many women today follow fashion, and it can endanger them. There are many phenomena of women not wearing the hijab, being open, and revealing their private parts to other men, which generally means that decent women will not show off this jewelry or even wear something that is unnatural to wear. This research discusses the meaning of tabarruj in the Tafsir of the Qur'an surah al-Ahzab verse 33 according to contemporary mufassir namely Wahbah Az-Zuhaili in his book of Tafsir Tafsir al-Munir. The aim of this research is to analyze how the verses about tabarruj are interpreted and what the forms of tabarruj are according to Wahbah Az-Zuhaili in Tafsir Al-Munir Munir. This research uses a literature review with a qualitative and technical approach. Descriptive analysis. The results of this research show that Wahbah Az-Zuhaili agrees with interpreting the tabarruj verses, namely the act of a woman displaying her jewelry to attract the attention of other people who are not her mahrim.